Evaluation of circulating cell-free nucleic acids in plasma as biomarkers of laryngeal cancer - Basak Yavuz; Ozge Cil; Akin Cayir (Cellular, Molecular and Biomedical Reports, 2024)
It has been aimed to compare the level of cell-free nucleic acids (DNA, RNA, and miRNA) concentrations in laryngeal cancer patients with the control group composed of healthy individuals. It has been utilized 46 patients with laryngeal carcinoma who were previously diagnosed and treated were included and 46 healthy individuals were included as a control group. Peripheral blood samples were obtained from all participants. DNA, RNA, and miRNA were fluorometrically measured. We applied Mann Whitney U test to compare both groups and the adjusted general lineal model to identify associations between nucleic acid concentrations and tumor stages.  Circulating cell-free microRNA and RNA concentrations in the laryngeal cancer patients were significantly different  (p<0.05). Most importantly, tumor stages were the main factor that altered miRNA concentration in circulation. Our findings support that circulating cell-free miRNA and RNA have potential to be associated with laryngeal cancer. Finally, cell-free miRNAs can be used as a tool to predict different stages of laryngeal cancer.